Improving the work productivity of MSME employees in Kampung Pia through competence, experience, and creativity - Cinta Finada; Vera Firdaus; Hasan Ubaidillah (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines the influence of competence, experience, and creativity on the work productivity of MSME employees in Kampung Pia. The research is motivated by variations in employee productivity among local MSMEs, which are believed to be closely associated with differences in human resource quality. Employing a quantitative descriptive approach, the study involved 100 MSME employees selected through a cluster sampling technique. Data were collected using a structured questionnaire comprising 36 measurement items and analyzed using the Partial Least Squares (PLS) method with SmartPLS. The findings demonstrate that competence, experience, and creativity each exert a positive and significant influence on employee productivity. Employees possessing stronger competencies, broader work experience, and higher levels of creativity tend to achieve superior productivity outcomes. Furthermore, the three factors collectively contribute to enhancing employee performance, underscoring the importance of both technical capabilities and innovative thinking in supporting MSME competitiveness. These findings highlight the strategic role of human capital development in improving productivity and suggest that MSME managers should prioritize continuous skill enhancement, experiential learning opportunities, and the cultivation of creativity to strengthen organizational performance and long-term business sustainability. Keywords: Competence; Experience; Creativity